2006
DOI: 10.1118/1.2361078
|View full text |Cite
|
Sign up to set email alerts
|

Step‐and‐shoot data acquisition and reconstruction for cardiac x‐ray computed tomography

Abstract: Coronary artery imaging with x-ray computed tomography (CT) is one of the most recent advancements in CT clinical applications. Although existing "state-of-the-art" clinical protocols today utilize helical data acquisition, it suffers from the lack of ability to handle irregular heart rate and relatively high x-ray dose to patients. In this paper, we propose a step-and-shoot data acquisition protocol that significantly overcomes these shortcomings. The key to the proposed protocol is the large volume coverage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
152
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 216 publications
(155 citation statements)
references
References 14 publications
2
152
0
1
Order By: Relevance
“…First, the amount of contrast material was not BMI-adapted in concordance with a large body of literature [1][2][3][4]6,8], although suggested by a few previous reports [9,10]. However, only the use of a fixed amount of contrast material enabled us to specifically evaluate the influence of BMI on image noise and coronary vessel attenuation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…First, the amount of contrast material was not BMI-adapted in concordance with a large body of literature [1][2][3][4]6,8], although suggested by a few previous reports [9,10]. However, only the use of a fixed amount of contrast material enabled us to specifically evaluate the influence of BMI on image noise and coronary vessel attenuation.…”
Section: Discussionmentioning
confidence: 93%
“…Bolus tracking was performed with a region of interest (ROI) placed into the ascending aorta. All CTCA examinations were performed on a LightSpeed VCT XT scanner (GE Healthcare) with prospective ECG-triggering [6] [17]. Axial images for attenuation calculations were reconstructed with a slice thickness of 0.6 mm, using a standard medium softtissue convolution kernel.…”
Section: Ct Coronary Angiographymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, concerns regarding the radiation exposure of patients undergoing CTCA have been raised, which prompted various dose reducing algorithms. One of the most efficient techniques for radiation dose reduction in CTCA is prospective electrocardiography (ECG)-gating, where radiation is only delivered at selected time points of the cardiac cycle [5]. First studies have shown that the lowdose technique for CTCA is accurate for the diagnosis of significant coronary stenoses as compared with CA [6].…”
Section: Introductionmentioning
confidence: 99%
“…The fully sampled region, the region covered by every view in the scanning, is less than the cylinder, with a height equal to the detector isocenter coverage. 14,15 To overcome this problem, we used extrapolation during the back projection process. The cone beam effect increases farther away from the isocenter and becomes more prominent with a larger FOV.…”
mentioning
confidence: 99%